2018
DOI: 10.1007/s12039-018-1530-4
|View full text |Cite
|
Sign up to set email alerts
|

$${\hbox {SO}}_{3}\hbox {H}$$ SO 3 H -functionalized magnetic $${\hbox {Fe}}_{3} {\hbox {O}}_{4}$$ Fe 3 O 4 nanoparticles as an efficient and reusable catalyst for one-pot synthesis of $${\upalpha }$$ α -amino phosphonates

Abstract: Nanomagnetic Fe 3 O 4 @SiO 2-SO 3 H (SO 3 H-MNPs) was prepared via grafting sulfonic acid on the silica-coated Fe 3 O 4 magnetite nanoparticles (MNPs). The catalytic activity of the prepared SO 3 H-MNPs was probed through the one-pot synthesis of N-hydroxy-α-amino phosphonates and α-amino phosphonates via three-component couplings of phenylhydroxylamine or amines with aldehydes and trialkyl phosphites at room temperature. The synthesized SO 3 H-MNPs were characterized by XRD, FT-IR, and SEM. The recoverability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Protection of Amine Groups Another important protection in organic strategies specially in multistep reactions is amine protection in which the N-tert-butoxycarbonyl (N-Boc) group due to some advantages is commonly used [17][18][19][20][21]. Herein, an efficient and time-consuming protocol was carried out by Hamadi et al using silica-supported BSA for the tert-butoxycarbonylation of various amines (9) under solvent free and room temperature conditions which illustrate in Scheme 4 [22,23]. The importance of N-formylation reactions have been obscured in the synthesis of pharmaceutically organic compounds containing the cores such as fluoroquinolones, imidazoles, 1,2-dihydroquinolines, formamidines and isocyanides [24][25][26][27][28].…”
Section: 12mentioning
confidence: 99%
See 2 more Smart Citations
“…Protection of Amine Groups Another important protection in organic strategies specially in multistep reactions is amine protection in which the N-tert-butoxycarbonyl (N-Boc) group due to some advantages is commonly used [17][18][19][20][21]. Herein, an efficient and time-consuming protocol was carried out by Hamadi et al using silica-supported BSA for the tert-butoxycarbonylation of various amines (9) under solvent free and room temperature conditions which illustrate in Scheme 4 [22,23]. The importance of N-formylation reactions have been obscured in the synthesis of pharmaceutically organic compounds containing the cores such as fluoroquinolones, imidazoles, 1,2-dihydroquinolines, formamidines and isocyanides [24][25][26][27][28].…”
Section: 12mentioning
confidence: 99%
“…The importance of N-formylation reactions have been obscured in the synthesis of pharmaceutically organic compounds containing the cores such as fluoroquinolones, imidazoles, 1,2-dihydroquinolines, formamidines and isocyanides [24][25][26][27][28]. Recently Hamadi et al reported a chemoselective N-formylation of amines (9) by catalytic activity of BSA in mild conditions which illustrated in Scheme 5 [23].…”
Section: 12mentioning
confidence: 99%
See 1 more Smart Citation